The Learners View About The Use Of Digital Technologies In Learning - Yunita Ningsih; Delfia Herwanis (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
Digital technology has completely changed how students access and interact with instructional information in today's schools. Digital tools are becoming more commonplace in the learning environment, which calls for a critical analysis of how students view and use these resources. This article seeks to explore how learners view the application of digital technologies to learning. Investigate the advantages that students feel they receive from using digital devices in the classroom and Determine the issues and worries students have with the inclusion of digital tools. A mixed-methods strategy was used to complete the study's goals, using quantitative and qualitative research techniques, there are survey, interview and literature review. The following are some of the major findings: Learners appreciate the advantages of digital technologies, including improved engagement, easy access to a plethora of knowledge, and individualized learning experiences. Effective educational practices have a favourable effect on students' experiences, and educators play a crucial role in influencing students' attitudes towards technology. The significance of a balanced strategy that takes advantage of technology's benefits while tackling its downsides is emphasised by learners. This study emphasises how important it is to take learners' opinions into account when creating digital learning environments. To maintain the relevance, engagement, and inclusivity of educational experiences, learner voices should be actively considered when making decisions on technology integration. Collaboration between academics, organisations, and politicians is required to strike this balance between utilising digital technologies' advantages and solving the problems they present. In the end, the study's findings provide insightful information for those involved in education, emphasising the necessity for a learner-centric strategy for integrating digital technology.